Gut microbiota: a promising new target in immune tolerance - Almansour, Nourah; Al-Rashed, Fatema; Choudhry, Khubaib; Alqaderi, Hend; Sindhu, Sardar; Al-Mulla, Fahd; Ahmad, Rasheed (Frontiers in Immunology, 2025)
Gut microbiota research has highlighted its pivotal role in human health and disease. Its composition is shaped by diet, genetics, age, and environmental factors. When the balance of these microbes is disrupted (dysbiosis), it can contribute to health problems like metabolic, inflammatory, and mental disorders. The microbiota supports digestion, fermentation, and vitamin production, which are essential for overall health. The gut microbiota has emerged as a critical modulator of immune function, with increasing evidence highlighting its role in establishing and maintaining immune tolerance. Despite significant advances in understanding the interactions between the gut microbiome and immune system, gaps remain in the literature regarding the specific mechanisms through which microbiota influences immune tolerance. This review aims to address these knowledge gaps by synthesizing current research on the microbiota impact on immune tolerance, emphasizing key factors such as microbial diversity, metabolic byproducts, and the microbiota interaction with immune cells, specifically focusing on the role of microbial tryptophan metabolites in PD-1/PD-L1 tolerance. We also highlight critical areas for future research, including the identification of microbial species or strains that can modulate immune tolerance, the influence of diet and environmental factors on microbiota composition, and the development of microbiota-based therapies. By bridging these gaps, this review seeks to provide a comprehensive understanding of the mechanistic role of microbiota immune tolerance and its potential as a novel therapeutic target for autoimmune and inflammatory diseases.